Efisiensi Sistem Coretax dalam Penerapan TER untuk Meningkatkan Kepatuhan Wajib Pajak pada BTS Consulting (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine the efficiency of implementing the CoreTax System in calculating Article 21 Income Tax using the average effective tax rate (TER) at BTS Consulting and its impact on taxpayer tax compliance. A descriptive qualitative approach was used in this study with data collection techniques through in-depth interviews and direct observation of tax reporting activities in the company. The results of the study indicate that the use of the CoreTax system simplifies the tax administration process through data processing automation, rate calculations that are directly adjusted to employee status, and automatic validation of potential input errors. This system also unifies the process of creating withholding tax certificates and billing in one reporting flow without the need to re-upload to the system again. Although there were technical challenges in the early stages of implementation, internal training and relaxation policies from the tax authorities supported the adaptation process. In conclusion, the CoreTax system is more efficient than the previous system.